Propriedades psicométricas da escala de esperança disposicional no contexto esportivo brasileiro - Moreira, Caio Rosas (2015)
The objective of this dissertation was to investigate the psychometric properties of the Dispositional Hope Scale (DHS) for Brazilian sport context. The present work was divide in two parts: Study 1 included the systematic review regarding the issue hope in the sporting context; and Study 2 was referring to validation process of the EED in sport. The Study 1 aimed to conduct a systematic review of literature on hope in sport context, verifying its influence in athletes' psychology process. The review consited of works that address hope in sport context. Following the guidelines of the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses), 24 articles were raised and analysed using meta-summarization, content analysis and meta-analysis. Most of the studies approached hope with motivation and performance. Burnout, negative affect and fear showed negative relationship with hope, as a group of studies on positive skills, showed a positive relationship with hope. Categories were created regarding the association of hope with other variables, as follows: performance, motivation, self-perception, coping strategies, feelings, stress and intervention, verifying that almost all variables have a positive correlation with hope, except the variables of stress group. It was concluded that hope has a positive relation to the athletes psychological process, favoring the sports performance and evidencing the low number of research on the hope sport relationship. Study 2 aimed to examine the psychometric properties of DHS in the sporting context. For this, participated adult male and female athletes, in both team and individual sports, participants in the final stage of the Parana Open Games of 2015. As an instrument, it was used the DHS and the Rosenberg Self-Esteem Scale. The study was divided into three stages (reliability and construct validity; internal validity; and external validity and temporal stability). The results evidenced that DHS showed satisfactory internal consistency; two-factor model in EFA; second order factor structure proven by CFA; positive correlations with self-esteem; as well as temporal stability of the scale. In conclusion, the DHS has satisfactory values of suitability and that is a valid instrument for the assessment of hope in the sporting context.